1) y' = (4x^3 - 3x^2 - 3x + 4)' = 12x^2 - 6x - 3
2) y' = (4x-3)(x-3)' = (4x-3)' * (x-3) + (4x-3) * (x-3)' = 4(x-3) + 4x - 3 = 4x - 12 + 4x - 3 = 8x - 15
3) y' = (4x^3 - 3x^2 + x - 1)' = 12x^2 - 6x + 1
y=
y'=
все остальные примеры аналогично, применяя таблицу производных
Пошаговое объяснение:
1) y' = (4x^3 - 3x^2 - 3x + 4)' = 12x^2 - 6x - 3
2) y' = (4x-3)(x-3)' = (4x-3)' * (x-3) + (4x-3) * (x-3)' = 4(x-3) + 4x - 3 = 4x - 12 + 4x - 3 = 8x - 15
3) y' = (4x^3 - 3x^2 + x - 1)' = 12x^2 - 6x + 1
y=![4x^{3} -3x^{2} -3x+4](/tpl/images/1355/0897/fa6fd.png)
y'=![(4x^{3} )'-(3x^{2} )'-(3x)'+(4)'=12x^{2} -6x-3](/tpl/images/1355/0897/1855a.png)
все остальные примеры аналогично, применяя таблицу производных
Пошаговое объяснение: